Social impact of churches and monasteries in Damascus in the Umayyad era (41-132 AH/661-749 A.M) (Journal of the College of Basic Education, 2022)
Damascus is the Kasbah of the Levant, the capital of the Umayyad caliphate, She has enjoyed an important place since the earliest times, thus making it the focus of the Islamic world. Different races of Muslims, supporters, Jews and others were annexed, and everyone was free to practise their religion, After establishing covenants for reconciliation between them and Muslims after the Islamic conques , a number of items included approval of their homes and churches They are protected under the Islamic rule in exchange for payment of the tribute tax for their heads and the departure from their lands. So the churches and monasteries were of interest to the Umayyad successors, so they took it to their comfort, It was also promised as a lodge for travelers and crossers, and the location of these monasteries between mountain peaks or cities, Ariaf and wilderness, And in every monastery there was a church where the Deranians prayed, It contains silos that accommodate monks, and has a range of facilities, including warehouses, dining houses and bookcases